Peranan Pendidikan Agama Islam dalam Pembinaan Perilaku Siswa di Sekolah Dasar - Athena Zulfa (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
This study aims to identify behavioral guidance for elementary school students and madrasah ibtidaiyah in East Java. The results showed: 1) specific strategies were not found in fostering student behavior based on Islamic religious education in primary schools and madrasah ibtidaiyah in East Java. Development of student behavior carried out in schools is still in general 2) strategies for developing student behavior must be developed in schools based on Islamic education to make Islamic religious education the main subject used to foster student behavior. Islamic education in addition to teaching religion, must also instill and familiarize good attitudes and behavior. Other important aspects that need to be considered in the framework of fostering effective behavior in schools are the vision, mission, and goals of the school, and togetherness. There is a clear and detailed program, covering all subjects and all teachers. There is a special facility and team support for the implementation of student behavior development programs based on the Islamic religion.